Changes in Protein O-GlcNAcylation During Mouse Epididymal Sperm Maturation - Tourzani, Darya A.; Paudel, Bidur; Miranda, Patricia V.; Visconti, Pablo E.; Gervasi, María G. (Frontiers in Cell and Developmental Biology, 2018)
After leaving the testis, sperm undergo two sequential maturational processes before acquiring fertilizing capacity: sperm maturation in the male epididymis, and sperm capacitation in the female reproductive tract. During their transit through the epididymis, sperm experience several maturational changes; the acquisition of motility is one of them. The molecular basis of the regulation of this process is still not fully understood. Sperm are both transcriptionally and translationally silent, therefore post-translational modifications are essential to regulate their function. The post-translational modification by the addition of O-linked β-N-acetylglucosamine (O-GlcNAc) can act as a counterpart of phosphorylation in different cellular processes. Therefore, our work was aimed to characterize the O-GlcNAcylation system in the male reproductive tract and the occurrence of this phenomenon during sperm maturation. Our results indicate that O-GlcNAc transferase (OGT), the enzyme responsible for O-GlcNAcylation, is present in the testis, epididymis and immature caput sperm. Its presence is significantly reduced in mature cauda sperm. Consistently, caput sperm display high levels of O-GlcNAcylation when compared to mature cauda sperm, where it is mostly absent. Our results indicate that the modulation of O-GlcNAcylation takes place during sperm maturation and suggest a role for this post-translational modification in this process.